Visual Management Design in Business Processes for Power Transformer Factories Using Virtual Obeya - Dony kurniawan; Ratna Sari Dewi (Eduvest - Journal of Universal Studies, 2026)
Power transformer factories are an Engineering to Order (ETO) industry where the products produced have small volume characteristics but many variants. This is due to the need for a power transformer that adjusts to the needs of the customer's electrical system so that each transformer is designed custom. This business process requires a very massive and rapid exchange of information. It is necessary to have a platform to make the distribution of information structured. Currently, Physical Obeya is implemented using a large space and a board containing important data that can be viewed by all cross-functional teams. However, this board still has some drawbacks to accessibility that require a physical presence and a complicated update process. So, virtualization on Physical Obeya was carried out. Virtualization is done by gathering several inputs from cross-functional teams and mapping them into a Value Proposition Canvas to identify the goals and advantages and disadvantages of Physical Obedience that has been carried out so far. Then, the design of virtualization in Physical Obeya is carried out by understanding the business processes in the company to identify what are the process checkpoints in a project into a database, and visualized in a way that takes into account human factors and cognitive ergonomics. Thus, virtual platforms can focus on users. Based on the results of these tests, the platform can be put to good use according to the previously identified objectives.